Legalitas Pencalonan Kepala Daerah Dari Unsur Tentara Nasional Indonesia Dan Polisi Republik Indonesia Dalam Pemilihan Kepala Daerah 2018 - Moh Khalilullah A. Razaq (Universitas Islam Indonesia, 2020)
This study aims to analyze the legality of the nomination of regional heads from the elements of Indonesian National Army (TNI) and Indonesian National Police (Polri) in the 2018 simultaneous regional elections. With problems formulation as follow : First, is the nomination of regional heads from elements of TNI and Polri in the 2018 simultaneous regional elections in line with the legislation? Second, what are the proper arrangements for regional head candidates from the elements of TNI and Polri in the 2018 simultaneous regional elections? This study uses a juridical-normative approach. In addition, this study also uses a field study approach based on the scope and identification of the existing problems. The results of the study concluded as follow: First, TAP MPR Number VII / MPR / 2000 on the Role of TNI and the Role of Police; Law Number 34 of 2004 on Indonesian National Army and Law Number 2 of 2002 Indonesian National Police determine that the TNI and Polri are impartial in political affairs and do not involve themselves in practical political activities. TNI and Polri can hold civilian positions after resigning or retiring from the TNI and Polri institutions, so that they do not conflict with the statutory regulations. Second, even though they have resigned, active members of the TNI and Polri who wish to run for regional head candidates should first wait for a gap of at least two years, to ensure the impartiality and maintain the morale of the TNI and Polri institutions.